Optimisation of parameters for obtaining milk-plant concentrates - Savchenko, Alexander; Grek, Olena; Skyibida, Valeriya; Onopriichuk, Olena; Pshenychna, Tetyana (My University, 2025)
A priority direction in the dairy processing industry is the development of innovative resource-saving technologies that enable raw material conservation, increased yield, and expanded product range. In particular, there is a growing demand for plant-based milk analogs in mixtures for producing milk-plant concentrates using accelerated technologies. The study aimed to determine the optimal parameters of the thermoacid coagulation process for milk-plant protein mixtures to obtain milk-plant concentrates and analyse their impact on the yield and qualitative characteristics of the final product. Milk-plant concentrates were obtained by thermoacid precipitation of proteins from a milk-plant mixture. The Box-Wilson central composite design method was used to optimise the parameters of concentrate production. It was established that thermoacid precipitation of proteins in a milk-plant mixture containing 35% whey-plant suspension with a water-to-solid ratio of 1:3 and a self-pressing duration of 30 min ensured a 36% transition rate of both milk and plant proteins into the concentrate. These parameters were 8-12% higher than those for protein precipitation from a mixture of skim milk and whey-plant suspension (20%) with water-to-solid ratios of 1:5 and 1:7. The addition of a 20% whey-plant suspension with a water-to-solid ratio of 1:7 and a curd self-pressing duration of 10 min resulted in the least protein destabilisation and the highest moisture content (78%) in the milk-plant concentrates. Analysis of the active acidity (pH) of the concentrates revealed a general trend: as the proportion of whey-plant suspension in the mixture increased from 20% to 40% and its water-to-solid ratio changed from 1:7 to 1:3, the pH decreased linearly. The lowest impact on water-holding capacity (72%) was observed under the following conditions: 20% whey-plant suspension, 1:7 water-to-solid ratio, and 10 min self-pressing duration. The obtained results allow for the regulation of qualitative indicators of milk-plant concentrates depending on their intended use, enabling the diversification of protein products with controlled moisture content, water-holding capacity, and active acidity. Пріоритетним напрямком у молочно-переробній промисловості є розробка інноваційних ресурсозберігаючих технологій, що дозволяють економити сировину, збільшувати вихід продукції та розширювати асортимент продукції. Зокрема, зростає попит на рослинні аналоги молока в сумішах для виробництва молочно-рослинних концентратів з використанням прискорених технологій. Метою дослідження було визначення оптимальних параметрів процесу термокислотної коагуляції молочно-рослинних білкових сумішей для отримання молочно-рослинних концентратів та аналіз їх впливу на вихід та якісні характеристики кінцевого продукту. Молочно-рослинні концентрати отримували методом термокислотного осадження білків із молочно-рослинної суміші. Для оптимізації параметрів виробництва концентрату було використано метод центрального композитного проектування Бокса-Вілсона. Встановлено, що термокислотне осадження білків у молочно-рослинній суміші, що містить 35% суспензії молочної сироватки та рослин, зі співвідношенням води до сухої речовини 1:3 та тривалістю самопресування 30 хвилин забезпечило 36% перехід як молочних, так і рослинних білків у концентрат. Ці параметри були на 8-12% вищими, ніж для осадження білка із суміші знежиреного молока та суспензії сироватки та рослин (20%) зі співвідношенням води до твердих речовин 1:5 та 1:7. Додавання 20% суспензії сироватки та рослин зі співвідношенням води до твердих речовин 1:7 та тривалістю самопресування сиру 10 хвилин призвело до найменшої дестабілізації білка та найвищого вмісту вологи (78%) у концентратах сироватки та рослин. Аналіз активної кислотності (pH) концентратів виявив загальну тенденцію: зі збільшенням частки суспензії сироватки та рослин у суміші з 20% до 40% та зміною її співвідношення води до твердих речовин з 1:7 до 1:3, pH лінійно зменшувався. Найменший вплив на вологоутримувальну здатність (72%) спостерігався за таких умов: 20% суспензія сироватки та рослин, співвідношення води до твердих речовин 1:7 та тривалість самопресування 10 хвилин. Отримані результати дозволяють регулювати якісні показники молочно-рослинних концентратів залежно від їх цільового використання, що дає змогу диверсифікувати білкові продукти з контрольованим вмістом вологи, вологоутримуючою здатністю та активною кислотністю.
Keywords: кафедра технології молока і молочних продуктів; thermoacid coagulation; термокислотна коагуляція; сироватка; молочно-рослинний концентрат; білкова суміш; whey; milk-vegetable concentrate; protein blend